2017
DOI: 10.1016/j.eats.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Bone Loss of the Shoulder Joint due to Recurrent Instability: Use of Fresh Osteochondral Distal Tibia and Humeral Head Allografts

Abstract: With increasing shoulder instability events, the likelihood of a bony lesion of the glenoid and/or humeral head rises. Although bone loss of either the glenoid or humeral head may result in recurrent instability, bipolar lesions have been shown, in particular, to result in a negative and additive effect on glenohumeral stability. In the case of a bipolar lesion comprising severe glenoid bone loss and an engaging, "off-track" Hill-Sachs lesion, the bony foundation of the glenohumeral joint is compromised and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…All 10 patients were male (Table 1). The average age of the time of surgery was 28 years (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The cohort had endured an average of 5.3 years (1-15) of anterior instability and have experienced on average 7 dislocations (4-16) before the combined humeral head reconstruction and Latarjet operation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 10 patients were male (Table 1). The average age of the time of surgery was 28 years (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The cohort had endured an average of 5.3 years (1-15) of anterior instability and have experienced on average 7 dislocations (4-16) before the combined humeral head reconstruction and Latarjet operation.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study has reported simultaneous Hill–Sachs and anteroinferior glenoid reconstruction. Haber et al 32 published a case report in which distal tibial allograft (DTA) was used for glenoid reconstruction together with allograft Hill–Sachs reconstruction. Their rationale for DTA over Latarjet is that the former has better joint congruity and denser trabecular matrix, making it an optimal graft.…”
Section: Discussionmentioning
confidence: 99%
“…A Latarjet was also indicated in the case of significant glenoid bone loss and/or significant bipolar lesions (bony lesions of both glenoid and humeral head). 16 If a player's career was at a pivotal point at which an incidence of recurrence may be career ending, 25 a primary Latarjet was considered. Similarly, in the case of a primary dislocation on the contralateral shoulder, a primary Latarjet was often considered to reduce the risk of recurrence and additional time out of competition.…”
Section: Patient Selectionmentioning
confidence: 99%
“…27 Patients younger than 20 years, generally the age group most susceptible to such dislocations, demonstrate a 95% rate of recurrence. 14,27 Combining this information with Nakagawa et al's 47 report that 60% of patients with traumatic anterior shoulder instability had bipolar lesions (glenoid and humeral head), the value of a procedure that can restore bony integrity to the glenohumeral joint is clear. Humeral head and distal tibial allografts (Figure 4) provide orthopaedic surgeons with 2 options for accomplishing this restoration.…”
Section: Fresh Distal Tibial and Humeral Head Ocasmentioning
confidence: 99%